2017
DOI: 10.1155/2017/1590653
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-Like Receptor 3 Single-Nucleotide Polymorphisms and Hepatitis C Virus Infection

Abstract: Toll-like receptor 3 (TLR3) plays a key role in innate immunity by recognizing pathogenic, double-stranded RNAs. Thus, activation of TLR3 is a major factor in antiviral defense and tumor eradication. Although downregulation of TLR3 gene expression has been mainly reported in patients infected with hepatitis C virus (HCV), the influence of TLR3 genotype on the risk of HCV infection, HCV-related cirrhosis, and/or hepatocellular carcinoma (HCC) remains to be determined. Single-nucleotide polymorphisms (SNPs) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Eradication of HCV infection involves coordinated effort between innate and adoptive immunity, as the innate immune responses initially, and later adaptive immunity becomes operational 8 weeks post‐infection . Initially, innate immunity recognises HCV via pattern recognition receptors (PRR) through TLRs, which target pathogen‐associated molecular patterns (PAMPs) found on HCV, thus augmenting immunity through upregulating IFN secretion and induction of IFN‐α‐inducible genes involved in antiviral and immune regulatory functions. The association of TLR with virological response to peg‐IFN plus RBV therapy in HCV‐infected patients explains the appearance of TLR4 and TLR2 as the top 10 treatment response related genes (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Eradication of HCV infection involves coordinated effort between innate and adoptive immunity, as the innate immune responses initially, and later adaptive immunity becomes operational 8 weeks post‐infection . Initially, innate immunity recognises HCV via pattern recognition receptors (PRR) through TLRs, which target pathogen‐associated molecular patterns (PAMPs) found on HCV, thus augmenting immunity through upregulating IFN secretion and induction of IFN‐α‐inducible genes involved in antiviral and immune regulatory functions. The association of TLR with virological response to peg‐IFN plus RBV therapy in HCV‐infected patients explains the appearance of TLR4 and TLR2 as the top 10 treatment response related genes (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with impaired TLR3-mediated responses show an elevated susceptibility to Herpes Simplex-1 Virus (HSV-1)-mediated encephalitis by encoding TLR3-deficient alleles [102,103], or by encoding deficient TRAF3, TBK1 and TRIF molecules, leading to impaired TLR-3 signaling [104][105][106]. In a Saudi Arabian population, the TLR3 rs78726532 SNP was strongly associated with Hepatitis B (HBV) and Hepatitis C (HCV) virus infections when compared to that in healthy control subjects [107,108]. The TLR3 rs5743314 C allele was also associated with HCV-related liver disease progression (cirrhosis and hepatocellular carcinoma) [107].…”
Section: Snps In Host Genes Affecting Iav Diseasementioning
confidence: 99%
“…In a Saudi Arabian population, the TLR3 rs78726532 SNP was strongly associated with Hepatitis B (HBV) and Hepatitis C (HCV) virus infections when compared to that in healthy control subjects [107,108]. The TLR3 rs5743314 C allele was also associated with HCV-related liver disease progression (cirrhosis and hepatocellular carcinoma) [107]. However, the functional effects of these SNPs seem to be unknown.…”
Section: Snps In Host Genes Affecting Iav Diseasementioning
confidence: 99%
“…Previous studies demonstrated that genetic factors play an important role in HCV infection, in addition to some well‐understood factors such as age and liver function . A significant association was found between HCV infection and gene polymorphisms in immune‐related genes, such as interleukin‐family, toll‐like receptor (TLR), patatin‐like phospholipase domain containing 3, interferon lambda 4, and inosine triphosphate pyrophosphatase . Given the important biological function of RLRs in HCV infection, it is essential to explore the potential influence between RLR gene polymorphisms and HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…12 A significant association was found between HCV infection and gene polymorphisms in immune-related genes, such as interleukin-family, toll-like receptor (TLR), patatin-like phospholipase domain containing 3, interferon lambda 4, and inosine triphosphate pyrophosphatase. [13][14][15][16][17][18][19][20][21][22] Given the important biological function of RLRs in HCV infection, it is essential to explore the potential influence between RLR gene polymorphisms and HCV infection. However, research on the association between mutations in RLR-related genes and HCV infection are scant currently.…”
mentioning
confidence: 99%